The Holocaust in Eastern Europe : at the epicenter of the final solution - Beorn, Waitman Wade 1977- (Perspectives on the Holocaust, 2018)
Beyond the pale: pre-war Jewish life in Eastern Europe -- The origins of the Nazi state -- Nazis and the imaginary East -- The Soviet interlude -- Poland: the Nazi laboratory of genocide -- War of annihilation: the invasion of the Soviet Union -- Ghetto life and death in the East -- Hitler's Eastern allies -- The Final Solution -- The kaleidoscope of Jewish resistance -- Perpetrators, collaborators, and rescuers